PENGARUH ATRIBUT TOKO ONLINE TERHADAP PERILAKU PEMBELIAN ONLINE KONSUMEN LAZADA INDONESIA - Hutami, Rr. Rieka F; Rahmah, Zenia (KINERJA, 2016)
AbstractThe number of Internet users in Indonesia is growing, making business conventional turning into a business online. For understand online consumer behavior patterns, companies need to know the factors that influence buying behavior online. The number of respondents in this study were 387 respondents who shopped online in the website Lazada Indonesia.co.id. Data were analyzed using SEM-PLS (Partial Least Square) and using software SmartPLS3. The results showed that the Site Commitment is the most significant variables that influence the purchasing behavior of online consumers Lazada Indonesia.Keywords: Online Stores Attributes, Online Purchase Behavior